TOLERANCE OF PEANUT GENOTYPES TO ACIDIC SOIL CONDITION - Kasno, Astanto; Taufiq, Abdullah; Trustinah, Trustinah (AGRIVITA Journal of Agricultural Science, 2013)
The acidic soil is generally less productive due to soil pH ranging from 3.1 to 5.0. However, it could be solved through soil amelioration, planting tolerant varieties to acidic soil condition, and a combination of both. Twenty peanut genotypes including two check varieties (Jerapah and Talam 1) were evaluated on dolomite-ameliorated and non ameliorated soil. In the greenhouse, the treatments were laid out in factorial design with four replications, while in the field using strip plot design with three replications. Assessment of tolerance was using Stressed Tolerance Index (STI) according to Fernandez (1992). Results showed that dolomite application at dose equivalent to 0.5 x exchangeable Al was optimal in improving peanut growth, and peanut yield on acidic soil. Lines of GH3 (G/92088/92088-02-B-2-8-1) and GH 4 (G/92088/ 92088-02-B-2-8-2) genotypes had high STI with average yield of 2.47 tha-1 and 2.62 t ha-1 of dry pods and potential yield of 4.05 t ha-1 and 3.73 t ha-1 of dry pods, respectively as well as check varieties (Jerapah and Talam-1). It is concluded that peanut genotype of G/92088//92088-02-B-2-8-1 and G/92088//920 88- 02-B-2-8-2 were adaptable and tolerance to acidic, and tolerance of peanuts on acidic soil condition were probably controlled by the buffering mechanisms. Keywords: peanut, acidic soil, tolerance